2021
DOI: 10.3390/ma14175027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Substrates on the Formability and Densification Behaviors of Cemented Carbide Processed by Laser Powder Bed Fusion

Abstract: Cemented carbide materials are widely applied in cutting tools, drill tools, and mold fabrication due to their superior hardness and wear resistance. Producing cemented carbide parts via the laser powder bed fusion (L-PBF) method has the advantage of fabricating complex structures with a rapid manufacturing speed; however, they were underdeveloped due to their low density and crack formation on the blocks. This work studied the effect of different substrates including 316L substrates, Ni200 substrates, and YG1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…These high-magnification pictures helped to find the tiny cracks on the blocks. It revealed that the cracks were inevitably generated on all specimens, similar to the previous studies [ 23 , 27 ]. The formation of cracks was mainly attributed to the brittleness of the cemented carbide.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These high-magnification pictures helped to find the tiny cracks on the blocks. It revealed that the cracks were inevitably generated on all specimens, similar to the previous studies [ 23 , 27 ]. The formation of cracks was mainly attributed to the brittleness of the cemented carbide.…”
Section: Resultssupporting
confidence: 88%
“…All specimens were fabricated by the L-PBF system (EOSINT M280, Munich, Germany), which has a fiber laser with a maximum power of 400 W and a spot size of 100 μm. A pure nickel substrate was used in this fabrication because our previous study had proven that the nickel substrate presented excellent adhesive bonding to the WC-17Co materials for a wide range of laser energy inputs [ 27 ]. Moreover, the substrate was pre-heated to 80 °C before the fabrication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substrate material can play an important role in SLM processing of cemented carbides. Liu et al [17] successfully made WC-17Co carbide with 96% relative density via the SLM process on Ni200 substrate, which was superior to the 316L stainless steel substrate. Li et al [18] have fabricated cemented carbides via laser melting deposition and obtained higher density and fewer cracks on the cemented carbide substrate compared with the 45# steel substrate.…”
Section: Introductionmentioning
confidence: 99%